Strategi Campaign Personalization Dalam Keberhasilan Pecah Telur PKB Pada Pemilu DPR-RI 2024 Di Daerah Pemilihan Jawa Barat - Vaza Sabila Ananda Rizqy; Wardani, Sri Budi Eko (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the winning strategy of the National Awakening Party (PKB) in gaining legislative seats in non-basic electoral districts (dapil) in the 2024 Election. The main focus of this study is the phenomenon of "broken eggs" in three electoral districts that recorded electoral deadlock for PKB during the reform era, until finally winning its first seat in the 2024 Election. Using the theoretical framework of Campaign Personalization from Söderlund (2024), this study dissects how the interaction between the dimensions of candidate campaign orientation contributes to individual and party vote acquisition. This qualitative research was conducted through case studies in three electoral districts with heterogeneous voter characteristics. The research findings indicate that PKB's success is driven by a combination of three integrative strategic dimensions. First, the person-oriented dimension that relies on the construction of religious authority, professional reputation, and a candidate profile that is accommodating to a spectrum of Islamic groups. Second, the constituency-oriented dimension through issue localization and "politics of presence" that is responsive to the sociocultural needs of constituents, both in traditional bases and urban residential areas. Third, the party-oriented dimension manifests the party's collective reputation through the synchronization of individual campaign narratives with the momentum of the Anies-Muhaimin (AMIN) national coalition. The analysis concludes that electoral victory in an open proportional representation system depends heavily on the candidate's ability to build a personal reputation aligned with the party's political momentum at the national level. This synergy has proven effective in penetrating new voter niches and breaking down electoral barriers in historically impenetrable areas.